2022
DOI: 10.3991/ijet.v17i13.32797
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Comprehensive Services of an Online Learning Platform Based on Artificial Intelligence

Abstract: With the college students having increasing needs for learning diversified knowledge and skills, online learning platforms for essential qualities enhancement have emerged one by one. However, due to lack of feedbacks from students, the comprehensive service quality of these platforms varies greatly. Therefore, it has certain practical significance to study how to evaluate the comprehensive services of online learning platforms. The current evaluation models are not suitable for online learning platforms, nor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…He, Y. et al [16] demonstrated that content and activity designs of network teaching can effectively improve learners' learning satisfaction, while object and evaluation designs could not. Yang, P. et al [17] established a comprehensive service Online Teaching Quality Evaluation: Entropy TOPSIS and Grouped Regression Model quality evaluation model of online learning that was composed of hierarchical and rough set-neural network evaluation to verify the validity of the built index system. A careful literature review revealed that many studies have applied the method of combining qualitative and quantitative analyses during the evaluation of university or online teaching quality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…He, Y. et al [16] demonstrated that content and activity designs of network teaching can effectively improve learners' learning satisfaction, while object and evaluation designs could not. Yang, P. et al [17] established a comprehensive service Online Teaching Quality Evaluation: Entropy TOPSIS and Grouped Regression Model quality evaluation model of online learning that was composed of hierarchical and rough set-neural network evaluation to verify the validity of the built index system. A careful literature review revealed that many studies have applied the method of combining qualitative and quantitative analyses during the evaluation of university or online teaching quality.…”
Section: Literature Reviewmentioning
confidence: 99%